Optimizing the Metacognitive Ability of Intelligent Deaf Children Through Innovative Learning - Yori, Dwianaresma; Fitriani, Wahidah; Yeni, Putri (Yayasan Minang Darussalam, 2025)
This research aims to optimize the metacognitive abilities of intelligent deaf children through innovative learning. This study uses a qualitative approach with a focus on literature analysis and learning practices. The results of the study show that deaf children have special challenges in the development of metacognitive skills, which has an impact on their learning ability. Innovative learning, including vocational learning, effective sign language teaching, and the implementation of the Multiple Intelligences theory, has been shown to improve the metacognitive abilities of deaf children. Strategies such as the use of visual aids, intensive non-verbal communication techniques, and individualized learning approaches were found to be effective. This research also reveals the importance of the role of teachers in developing special skills to teach deaf children. In conclusion, the optimization of the metacognitive abilities of intelligent deaf children can be achieved through the application of innovative learning methods tailored to their specific needs.